Visualization analysis of reciprocating‐screw plastication process of glass fiber‐reinforced resins in a glass‐inserted heating cylinder. Issue 4 (5th December 2018) - Ma, Sai; Shibata, Kazuyuki; Yokoi, Hidetoshi
Abstract : One challenge in injection molding of long fiber‐reinforced resins is minimizing the fiber breakage during resin plastication and resin flow into a mold. Such fiber breakage reduces the strength of the molded product. Reciprocating plastication is subjected to periodic positional fluctuations of the screw and cylinder in the molding cycle. In this study, visualization experiments were conducted on the reciprocating plastication of long glass fiber (GF)‐reinforced polypropylene with 50 wt% GF. It was found that: (1) temporary voids form in the resin during the metering process, and the pellets rotate from an orthogonal to parallel orientation in the flight direction; (2) length of the weight‐averaged fiber temporarily decreased in the middle stage of the injection process; (3) length of the weight‐averaged fiber was most strongly influenced by the waiting time; and (4) for constant waiting time, the fiber breakage could be minimized by lowering the rotation speed, lowering the back pressure, and shortening the charge stroke. POLYM. ENG. SCI., 59:846–853, 2019. © 2018 Society of Plastics Engineers